ENDEMIC Pemphigus foliaceus AT UCAYALI DEPARTMENT – PERU. REPORT OF 16 CASES - GALARZA, CARLOS (2002)
We report 16 cases of Pemphigus foliaceus occurred at Ucayali, department of Peru. Most of them came from Coronel Portillo, Ucayali’s province (94%), and half of them from Campo Verde district. Eighty per cent belonged to rural areas, 56% were females and 7 children were affected (43%). All patients had generalized skin involvement without mucous membranes compromise. Nikolsky sign was present in 50%. In all cases skin biopsy showed subcorneal acantholysis and only 40% presented pemphigus positive immunofluorescence.